2020
DOI: 10.3390/ijerph17228347
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Is a Risk Factor for Suffering and for in-Hospital Mortality with Pulmonary Embolism. A Population-Based Study in Spain (2016–2018)

Abstract: (1) Background: The relationship between type 2 diabetes (T2DM) and pulmonary embolism (PE) has not been well stablished so far. We aim to analyze incidence, clinical conditions and in-hospital mortality (IHM) according to the presence of T2DM among patients hospitalized for suffering from PE. The factors associated with IHM were identified. (2) Methods: Patients aged ≥40 years hospitalized for PE from 2016 to 2018 included in the Spanish National Health System Hospital Discharge Database were analyzed. Depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…In accordance with the present results, a recently published analysis of the Spanish National Health System Hospital Discharge Database in the timescale 2016-2018 comprising 47,190 patients aged ≥40 years who were hospitalized due to PE showed that diabetes was also associated with increased inhospital mortality (OR 1.15, 95% CI 1.05-1.26) 21 . These results from Spain (2016-2018) confirmed a former analysis comprising data of >120,000 PE patients in which diabetes was also related to higher in-hospital mortality (men OR 1.22, 95% CI 1.12-1.32; women OR 1.24, 95% CI 1.15-1.33) 47 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with the present results, a recently published analysis of the Spanish National Health System Hospital Discharge Database in the timescale 2016-2018 comprising 47,190 patients aged ≥40 years who were hospitalized due to PE showed that diabetes was also associated with increased inhospital mortality (OR 1.15, 95% CI 1.05-1.26) 21 . These results from Spain (2016-2018) confirmed a former analysis comprising data of >120,000 PE patients in which diabetes was also related to higher in-hospital mortality (men OR 1.22, 95% CI 1.12-1.32; women OR 1.24, 95% CI 1.15-1.33) 47 .…”
Section: Discussionsupporting
confidence: 92%
“…Besides the association of diabetes with the development of VTE, diabetes is a well‐recognized important driver for cardiovascular morbidity and mortality 7 , 41 , 42 , 43 , 44 , 45 . Nevertheless, data on the impact of diabetes on mortality and other adverse outcomes of PE patients are sparse and contradictory 20 , 21 , 22 . Although, in accordance with the present results, the majority of studies showed an increased risk of adverse outcomes and especially mortality among PE patients with diabetes, other studies were not able to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that the incidence of pulmonary embolism was particularly high in type 2 diabetes patients. 26 The underlying mechanism in such cases might be the innate activation of hyperglycemia that leads to abnormal coagulation and impaired fibrinolysis and thus increasing the risk of thrombosis. 27,28 This case report presented a 74-year-old female patient with postoperative pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%